Analysis of Deflection in Composite Bridge Girder Under Live and Dead Load Using SAP2000 - Susanty handayani; Jeffrey Victory; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2025)
The process of building a transportation infrastructure presents a unique challenge in the field of civil engineering. Bridges play an important role in supporting human mobility and transportation, as well as in delivering goods and services to various locations. A bridge structure must not suffer excessive deflection to have good service capabilities. This research seeks to find the amount of deflection of composite girder under live load and dead load. By inserting the load that occurs, this study wants to identify the deflection that happens using SAP2000 software. SAP200 is a sophisticated software application widely used in the field of structural engineering for the analysis and design of various types of structures. SAP2000 enables engineers to evaluate the behaviour of structures under different loading conditions, including static and dynamic loads, ensuring that designs meet required safety and performance standards. The findings show that based on the RSNI T-03-2005 Standard, the maximum deflection tolerance is L/240, where L is known as the total bridge span, which is 17.5 cm, while after being analysed by SAP2000, it is known that the total deflection that occurred on the composite girder is 17,2 cm. The findings underscore the importance of using advanced simulation tools like SAP2000 to predict structural behaviour accurately. This research highlights the necessity of precise deflection analysis in civil engineering projects to ensure that transportation infrastructure can withstand the loads they will encounter during their service life. This research is designed to serve as a reference for challenges discovered for future research.